Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Xiaomi - Rika Ernawati; Axel Giovanni (Jurnal Bintang Manajemen, 2023)
As the world of technology develops, various kinds of smartphones appear on the market, so that this makes competition even tighter. The research aims to determine the effect of price and product quality on Xiaomi smartphone purchasing decisions. The population used in this study were students who are domiciled in Magelang Regency with a sample of 100 respondents. The sampling technique used in this research is purposive sampling technique. Based on the results of the analysis that has been done, it is concluded that price (X1) has a positive but not significant influence on purchasing decisions. While it is known that the product quality variable (X2) has a positive and significant influence on purchasing decisions.